2018
DOI: 10.1038/s41416-018-0009-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of obesity-related risk factors in the aetiology of glioma

Abstract: BackgroundObesity and related factors have been implicated as possible aetiological factors for the development of glioma in epidemiological observation studies. We used genetic markers in a Mendelian randomisation framework to examine whether obesity-related traits influence glioma risk. This methodology reduces bias from confounding and is not affected by reverse causation.MethodsGenetic instruments were identified for 10 key obesity-related risk factors, and their association with glioma risk was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 36 publications
(47 reference statements)
1
27
0
Order By: Relevance
“…This study encompassed 12,488 cases and 18,169 controls. This study found little evidence that indicated that obesity-related factors contribute to glioma ( Disney-Hogg et al, 2018b ).…”
Section: Mr In Glioma Researchmentioning
confidence: 64%
See 1 more Smart Citation
“…This study encompassed 12,488 cases and 18,169 controls. This study found little evidence that indicated that obesity-related factors contribute to glioma ( Disney-Hogg et al, 2018b ).…”
Section: Mr In Glioma Researchmentioning
confidence: 64%
“… Disney-Hogg et al (2018b) carried out an MR analysis to interrogate the observed association between obesity-related factors and risk of glioma. The authors identified variants that were robustly associated with 10 key obesity-related factors: 2-h post-challenge glucose, BMI, fasting glucose, fasting insulin, HDL cholesterol, LDL cholesterol, type-2 diabetes, total cholesterol, triglycerides and waist-hip ratio.…”
Section: Mr In Glioma Researchmentioning
confidence: 99%
“…This finding contrasts with our earlier work which found no evidence for an association; however, the previous analysis was based on fewer SNPs (26 vs 44). 18 Genetically predicted plasma total TG also showed a suggestive association with risk of GBM (OR SD = 0.87, 95% CI: 0.76-0.99, P = 0.030). Leave-one-out analysis showed that both LDL and TG associations were unstable.…”
Section: Cardiometabolic and Inflammatory Factorsmentioning
confidence: 93%
“…We considered only continuous traits, as analysis of binary traits (such as disease status) with binary outcomes in 2-sample MR frameworks can result in inaccurate causal estimates. 18,19 The analysis was restricted to SNPs associated at genome-wide significance (ie, P ≤ 5 × 10 −8 ) in individuals of European ancestry, to satisfy the MR assumption that genetic variants are associated with the modifiable risk factor. 22 To avoid collinearity between SNPs for each trait, correlated SNPs were excluded using the MR-Base database (linkage disequilibrium threshold, r 2 ≥ 0.01) within each trait, with SNPs with the strongest effect size retained.…”
Section: Genetic Instruments For Putative Risk Factorsmentioning
confidence: 99%
“…In contrast, given that the Central LHIN had the lowest trend, it can be inferred that disease risk for this health unit progressed the slowest over the period of study. As illustrated in Figure 4, six of the twelve LHINs (i.e., IDs 2,6,9,10,11,12) had local trends which were greater than γ. The space-time random effect δ is equivalent to the difference between the temporal trend of an individual LHIN and the mean trend γ of the entire region [31].…”
Section: Spatio-temporal Analysismentioning
confidence: 99%